The Effect of Concrete Quality on Structural Period - Fandel Maluw; Hendrie Joudie Palar; Don Kabo; Herman Tumengkol; Teddy Takaendengan (Jurnal Multidisiplin Madani, 2024)
An important consideration in structural calculations is a structure's vibration period, which establishes the size of the seismic stresses applied during the design phase. North Sulawesi falls within the category of high-risk earthquake region. The formula for calculating the vibration period, as outlined in SNI 03-1726-2012 is based on Goel and Chopra's (1997) approach and ASCE seismic standards. Nevertheless, SNI 03-1726-2012's formula has a notable limitation: it applies the same approach to all earthquake zones, regardless of whether the area is high-risk or low-risk. This study aims to develop a structural period formula tailored following the SNI 03-1726-2012 earthquake design guidelines and to investigate how the quality of the concrete affects the structural lifespan. Three-dimensional structural modeling of typical structures with floors is used in the study. heights of 4 meters and widths of 4 meters, specifically focusing on mid-rise reinforced concrete buildings with 12 floors. Structural modeling is conducted using the ETABS software, and regression analysis is performed on the resulting structural period values to derive the most accurate formula. The regression analysis yielded two optimal formulas, each with a correlation value of 98%: T=0.105H0.785T = 0.105 H^{0.785}T=0.105H0.785 and T=0.311n0.785T = 0.311 n^{0.785}T=0.311n0.785. The findings indicate that lower concrete quality leads to an increased structural period, albeit with a smaller overall impact. Thus, concrete quality significantly influences the structural period